Strategi Humas Panwaslu Kecamatan Maja Dalam Meningkatkan Kepercayaan Publik Sebagai Lembaga Pengawas Pemilu 2024 - Lomri, Muhamad; Fatimah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
The process of holding elections cannot be separated from various problems that arise from the community, voters and election organizers. This research aims to find out the Public Relations strategy of the Maja District Panwaslu in increasing public trust in Maja District and to find out how to carry out the public relations work of the Maja District Panwaslu. The type of research used is qualitative and the type of research used is descriptive qualitative. Data collection techniques use observation, interviews and documentation. The research results show that the Maja District Panwaslu's public relations strategy in increasing public trust uses Rosady Ruslan's theory, namely Operational Strategy, Persuasive and Educative Strategy, and Collaboration Strategy. Maja District Panwaslu in its strategy to increase public trust is able to process social media such as Facebook, Instagram and Tiktok. Apart from that, Public Relations is also actively carrying out activities to collaborate and increase support with external parties. Public Relations is also active in educating through socialization both directly and via social media posted by Maja District Panwaslu public relations. The next step is to shape the public's perspective on the Maja Subdistrict Panwaslu by declaring the tag line "Let's supervise together". The results of this research show how the Maja Subdistrict Panwaslu's public relations strategy has increased public trust. in carrying out public relations activities, namely, public relations who can work together in realizing every collaborative public relations program with several aspects that make public relations activities run well. In carrying out the Public Relations work program to increase public trust, it has been carried out, but there are factors that support and hinder the implementation of the program.